Propuesta para la implementación de actividades agro turísticas en la finca La Esperanza ubicada en el recinto San Miguel, cantón Quinsaloma, provincia de Los Ríos - Alarcón Gaibor, Jessenia Paola (2014)
The proposal for the implementation of agro-tourism activities are conducted on the farm “La Esperanza” 132msnm , is located in San Miguel Canton Quinsaloma enclosure in the province of Los Ríos this project was based on the proposal to implement agritourism activities to supplement agricultural activity is performed on the farm for the project field trip was made to make the diagnosis of the area and inventory attractions are there in the farm and tourist facilities are there this was done by applying tabs MINTUR 2004 where detailed each of the attractions . Surveys were conducted to determine the acceptance of the project , so 382 surveys of the population of Quevedo where it was found that 82% of respondents would like to do agritourism activities in the La Esperanza were applied. What determines the project would have a good acceptance in the tourism market. The proposed activities are conducted to analyze the potential of each of the attractions and the possibility exists for the implementation of these activities such as: bird watching , demonstration and agricultural planting , hiking , wine tasting and participation in product development , observation of agricultural products. All these activities were offered in this project as they have the material necessary for the implementation of these activities, and the farm has a path " YuraHatu " name is written in Kichwa meaning large tree and has an area of 313.90 meters of travel and shows no difficulty to be traveled because the entire surface is flat making event for people of all ages.